The Boma: How to stop drought aid 'coming with the vultures' - International Livestock Research Institute (International Livestock Research Institute, 2022)
"You guys are coming when we have really suffered, when we have lost half of our herd and also when the vultures are descending from the sky." So said a Kenyan pastoralist at a meeting about drought response. What is being done to anticipate drought, rather than to deal with the consequences? In this episode we look at the effects of the ongoing drought in the Horn of Africa, with 17 million people facing hunger and a fifth rainy season on the way.